THE INFLUENCE OF WORK MOTIVATION AND TRAINING ON PERFORMANCE THROUGH MARKETING EMPLOYEE COMPETENCE AT PT. HADJI KALLA - mutmainnah (Scientium Management Review, 2022)
Work motivation is a desire in a person that causes that person to do work. Meanwhile, training is an effort to improve employee performance in their current job or other jobs they will hold. This study aimed to determine how much work motivation and training affect the performance of marketing employees at PT. Hadji Kalla through competency. Respondents in this study amounted to 38 marketing employees with details of men and women. Data collection techniques using questionnaires with descriptive quantitative methods. The questions displayed on the questionnaire are questions using a Likert scale of 1-5. The analysis phase in this study begins with the research instrument, namely by collecting data and processing the data obtained in the questionnaire by giving the weight of each statement based on a Likert scale, as well as carrying out validity tests, reliability tests, normality tests, and regression tests. The regression test used is multiple regression. In its implementation, data processing was carried out with the help of the SPSS 23 program. The path analysis method was used to test the effect of mediation (intervening). The research results show (1) work motivation has a positive and significant effect on competence; (2) training has a positive and significant effect on competency; (3) work motivation has a positive and significant effect on performance; (4) training has a positive and insignificant effect on performance; (5) competence has a positive and significant effect on performance; (6) work motivation has a positive and significant effect on performance through competence; (7) training has a positive and significant effect on performance through competence.